Blocking substance P signaling reduces musculotendinous and dermal fibrosis and sensorimotor declines in a rat model of overuse injury. (1st November 2020) - Barbe, M.F.; Hilliard, B.A.; Fisher, P.W.; White, A.R.; Delany, S.P.; Iannarone, V.J.; Harris, M.Y.; Amin, M.; Cruz, G.E.; Popoff, S.N.
ABSTRACT: Purpose/Aim : Substance P-NK-1R signaling has been implicated in fibrotic tendinopathies and myositis. Blocking this signaling with a neurokinin 1 receptor antagonist (NK1RA) has been proposed as a therapeutic target for their treatment.Materials and Methods : Using a rodent model of overuse injury, we pharmacologically blocked Substance P using a specific NK1RA with the hopes of reducing forelimb tendon, muscle and dermal fibrogenic changes and associated pain-related behaviors. Young adult rats learned to pull at high force levels across a 5-week period, before performing a high repetition high force (HRHF) task for 3 weeks (2 h/day, 3 days/week). HRHF rats were untreated or treated in task weeks 2 and 3 with the NK1RA, i.p. Control rats received vehicle or NK1RA treatments.Results: Grip strength declined in untreated HRHF rats, and mechanical sensitivity and temperature aversion increased compared to controls; these changes were improved by NK1RA treatment (L-732, 138). NK1RA treatment also reduced HRHF-induced thickening in flexor digitorum epitendons, and HRHF-induced increases of TGFbeta1, CCN2/CTGF, and collagen type 1 in flexor digitorum muscles. In the forepaw upper dermis, task-induced increases in collagen deposition were reduced by NK1RA treatment.Conclusions : Our findings indicate that Substance P plays a role in the development of fibrogenic responses and subsequent discomfort in forelimb tissues involved in performing a high demand repetitive forceful task.